The Implementation of Blockchain Technology in the Criminal Justice System: Opportunities, Challenges, and Its Implications for Transparency and Accountability - Ardian, Rosa Eka Putri; Rozi, Fachrur; Soetikno, Noela (LPPM Universitas Sains dan Teknologi Komputer, 2025)
On the contrary, the criminal justice system in Indonesia remains embroiled in challenges such as transparency, accountability, and efficiency due to heavy reliance on manual documentation and convoluted bureaucratic procedures. This study intends to analyze the opportunities, challenges, and implications for the enhancement of transparency and accountability in the criminal justice system through blockchain technology. Data were collected through in-depth interviews, documentation, and participatory observation involving 15 informants from various legal institutions employing a descriptive qualitative and case study approach. Most informants were in favor of implementing blockchain to improve the transparency and integrity of legal data, although some institutional resisters and regulatory uncertainties exist. The originality of this research is primarily due to the integration of the technical, social, and legal perspectives in its interdisciplinary context. Practical implications are revealed for urgent policy reform, training of human resources, and infrastructure for a digital technology base towards enabling transformation in the judiciary.